Teachers’ Psychological Foundations in Enhancing Student Motivation and Creativity in Primary Schools: A Literature Review - Nurmayani; Putri Adilah Rahmadani; Novia Mawla Nisa; Lutfiah Gracia; Baihaqi Alexsius Silalahi (PT. Anagata Sembagi Education, 2025)
In primary education, student motivation and creativity often remain underdeveloped despite curricular innovations. This study addresses this issue by examining the role of teachers’ psychological foundations including their beliefs about learning, motivational literacy, and creative self-concept in shaping instructional practices that foster engagement and creativity in young learners. Guided by Self-Determination Theory (SDT), the research aimed to construct and validate a conceptual framework linking teacher psychology to motivating instructional support, student engagement, and creative outcomes. A qualitative constructivist grounded theory design was employed, involving semi-structured interviews, classroom observations, and document analysis. Participants consisted of primary school teachers with at least three years of experience, complemented by input from school leaders and student focus groups. Data analysis followed a coding cycle from initial open coding to theoretical integration, with triangulation and member checking ensuring trustworthiness. Findings revealed a four-stage pathway model: teacher psychological foundations, motivating instructional support, students’ need-satisfying experiences, and creative learning expressions. The results emphasize that autonomy-supportive and structured practices such as providing meaningful choices, explanatory feedback, and scaffolded open tasks significantly enhance student engagement and creativity. Moreover, teacher self-efficacy and tolerance for creative uncertainty emerged as mediators that determine whether psychological beliefs are enacted in practice.In conclusion, the study highlights that cultivating teachers’ psychological resources is essential for sustaining student motivation and creativity in primary classrooms. Professional development should therefore prioritize efficacy-building, creative identity, and integrated autonomy-supportive practices to strengthen long-term pedagogical impact.